An Efficient Brain Tumour Extraction in MR Images using Ford-Fulkerson Algorithm - C, Latha; Perumal, K. (Transactions on Engineering and Computing Sciences, 2016)
Brain tumor division intends to discrete the diverse tumor tissues, for example, dynamic cells, necrotic core,and edema from typical cerebrum tissues of White Matter (WM), Gray Matter (GM), and Cerebrospinal Fluid (CSF). MRI-basedbrain tumor division studies are drawing in more consideration lately because of non-invasiveimaging and great delicate tissue difference of Magnetic Resonance Imaging (MRI) pictures. With the improvement of very nearly two decades, the inventive methodologies applying PC supported strategies for the sectioning brain tumor are turning out to be more develop and coming closer to routine clinical applications. The reason for this exploration work is to give a far-reaching review to MRI-based brain tumor division techniques. To consider and characterize the tumor pictures, a couple of well-known Edge Detection Techniques have been proposed as of late. This examination work has distinguished KWT (K-Means, Watershed, and Texture) Segmentation Technique and executed and contemplated. From our test comes about, this examination work uncovered that this model neglects to make productive groups order force causes poor tumor characterization precision. This is one of the real issues to anticipate the tumor design and to address this issue, the Ford-Fulkerson Segmentation Technique is proposed and concentrated altogether as far as Mean Squared Error (MSE), Peak Signal to Noise Ratio (PSNR) and Classification Accuracy. Results set up that the proposed Ford-Fulkerson Segmentation Technique beats KWT in terms of Mean Squared Error (MSE), Peak Signal to Noise Ratio (PSNR) and Classification Accuracy.